Lavender and Purple Revolution: A review on the crop potential to boost and empower farming communities of North-Western Himalayas - Sharma, A; Sharma, N; Deep, N; Thaneshwari; Pandav, A K; Mondal, R (Plant Science Today, 2025)
Lavender (Lavandula spp.), a perennial flowering plant known for its distinctive aroma and medicinal properties, has been popularized all over the world. Lavender has its depictions in the ancient literature of Greeks and Romans as an herb with calming, antibacterial and anti-inflammatory properties which can help with stress relief, sleep, skin care and overall wellness. France, Bulgaria and India are the major lavender producers, with the latter experiencing a significant upsurge in commercial cultivation as a part of the Purple Revolution in recent years. With the objective of empowering farmers through improved socioeconomic development, higher income and sustainable farming, the Indian government launched the ‘Purple Revolution’ under CSIR Aroma Mission in the Union Territories of Jammu and Kashmir and Himachal Pradesh. Lavender cultivation has improved environmental sustainability by fostering biodiversity, reducing soil erosion and adding richness to the agricultural landscape of India. Lavender cultivation has huge commercial potential as it is becoming an important component of a number of medicinal and aromatic industries due to increased consumer demand for natural and organic products. Hence, the expansion of lavender cultivation during the Purple Revolution offers improved agri-entrepreneurship opportunities for international trade and financial prosperity for farming communities.